(untitled) (Research, Society and Development, 2021)
The tourism sector has shown sustainable growth in recent years, observing both the Brazilian and the world scenario. Although the global pandemic caused by COVID-19 interrupted the sector’s annual growth sequence and established tourism as the sector most affected by the pandemic, studies indicate that the second half of 2021 will be related to the beginning of the sector’s recovery phase and tourism of nature is pointed out as the most attractive niche in the recovery phase. On the other hand, the tourism sector has a huge potential for technological innovation and proposals aligned with Tourism 4.0 can bring even more strength in the post-pandemic. This work proposes a solution based on Internet of Things, Cloud Computing and Mobile Devices to help nature tourism. The solution allows tourists to observe via video streaming a remote point of visitation and assess the local weather conditions in real time, allowing for better planning of visitation and displacement. The study included the installation of 4 (four) monitoring stations in tourist spots in the state of Pernambuco and carried out an initial validation of the proposal with a small group of potential users of the solution. According to the obtained results, the monitoring stations provide more accurate information compared to existing services and the application was well evaluated by potential users.